A case report on anesthesia management for a patient with deep neck space infection (retropharyngeal and parapharyngeal abscess) - Aastha Jindal; Amit Kumar; Kamlesh Kunwar Shekhawat; Parul Sharma (Wolters Kluwer Medknow Publications, 2022)
A 44-year-old woman complained of neck swelling, discomfort, and swallowing difficulties. She was admitted to the hospital on an emergency basis for incision and drainage. Deep neck space infection was diagnosed using a neck X-ray, ultrasonography, and contrast enhanced computed tomography. The successful anesthetic management of this patient at the Pacific Institute of Medical Sciences in Udaipur is presented here.